Cegah Stunting Tumbuh Penuh Cinta Di Desa Seduri Kecamatan Mojosari Kabupaten Mojokerto - Atik Sri Wulandari; Popharina Berlianda; Tansatrisna Vony Rei Siswanto; Muhammad Rifky Ramadhan; Putri Nafisah Rizqi; Elmi Al Ghifany Kautsar; Agshal Almachzumi Andili; I Gede Paskha Yustiana; Komang Kuntari; Nabhila Annisa Rizqi N A; Wike Herawaty; Nur Khamidah (Jurnal Riset Multidisiplin Edukasi, 2026)
Stunting is a chronic nutritional problem that can affect children’s physical growth and cognitive development. One of the efforts to prevent stunting is by improving community knowledge, especially among mothers of toddlers. The health education activity titled “Cegah Stunting Tumbuh Penuh Cinta” was conducted at Posyandu Seduri, Mojosari District, Mojokerto Regency, on February 12, 2026, involving 30 mothers with toddlers. The method used was health education through lectures, discussions, and leaflet distribution, with evaluation using pre-test and post-test. The results showed an increase in the average knowledge score from 65 to 85 after the counseling. The proportion of participants with good knowledge increased from 26.7% to 73.3%, while poor knowledge decreased from 33.3% to 6.7%. This indicates that health education was effective in improving mothers’ knowledge about stunting and its prevention.